Mechanisms involved in the long-term modulation of tyrosine hydroxylase by endothelins in the olfactory bulb of normotensive rats - Nabhen, Sabrina Laura (2011)
The olfactory bulbs play a relevant role in the interaction between the animal and its environment. The existence of endothelin-1 and -3 in the rat olfactory bulbs suggests their role in the control of diverse functions regulated at this level. Tyrosine hydroxylase, a crucial enzyme in catecholamine biosynthesis, is tightly regulated by short- and long-term mechanisms. We have previously reported that in the olfactory bulbs endothelins participate in the short-term tyrosine hydroxylase regulation involving complex mechanisms. In the present work we studied the effect of long-term stimulation by endothelins on tyrosine hydroxylase in the rat olfactory bulbs. Our findings show that endothelin-1 and -3 modulated catecholaminergic transmission by increasing enzymatic activity. However, these peptides acted through different receptors and intracellular pathways. Endothelin-1 enhanced tyrosine hydroxylase activity through a super high affinity ETA receptor and cAMP/PKA and CaMK-II pathways, whereas, endothelin-3 through a super high affinity atypical receptor coupled to cAMP/PKA, PLC/PKC and CaMK-II pathways. Endothelins also increased tyrosine hydroxylase mRNA and the enzyme total level as well as the phosphorylation of Ser 19, 31 and 40 sites. Furthermore, both peptides stimulated dopamine turnover and reduced its endogenous content. These findings support that endothelins are involved in the long-term regulation of tyrosine hydroxylase, leading to an increase in the catecholaminergic activity which might be implicated in the development and/or maintenance of diverse pathologies involving the olfactory bulbs.